Lexical algorithmic resistance: Tactics of deceiving Arabic content moderation algorithms on Facebook - Reham Hosny; Mohamed A Nasef (Big Data & Society)
This study examines the lexical tactics of algorithmic resistance employed by Arab users to deceive Facebook content moderation algorithms in the case of censoring pro-Palestinian voices on Facebook, a phenomenon particularly conspicuous during the Palestine–Israel incidents of evicting East Jerusalem's Sheikh Jarrah neighbourhood in May 2021. It has since escalated, becoming increasingly pronounced with the ongoing war that commenced on 7 October 2023, known as the ‘Operation Al-Aqsa Flood’ and continues to unfold to the present day. To achieve this aim, Facebook data scraping was used to extract comprehensive insights on the most frequent lexical resistance techniques, the most used resistance keywords, the geographical mapping of users and the related socio-political context. This study draws upon critical perspectives from data colonialism, resistance studies, critical platform studies and digital humanities to propose the concept of lexical algorithmic resistance as a conceptual framework for understanding the dynamics of language-based algorithmic resistance. By elucidating how language becomes a site of resistance, this study contributes to perspectives that deepen our understanding of power dynamics and resistance tactics in the face of data colonialism and highlights the dual nature of digital tools, which can be wielded both as instruments of oppression and tools of resistance. The study revealed the diversity of lexical algorithmic resistance techniques employed, the keywords of resistance utilised in the Arabic sphere and the variations thereof at spatial and regional levels.